The influence of thermal ageing on the flow-stress of copper traces on PCB's. (August 2019) - Yuile, Adam; Wiese, Steffen
Abstract: This study focuses on the onset of plastic flow in different copper as processed materials. The tested copper sheets varied as to how they were manufactured and their post-manufacturing treatments, namely annealing. Tensile tests were conducted at 24 °C, 60 °C, 100 °C, 150 °C inside a temperature controlled test chamber on thin copper specimens. Each material was assessed as received from the manufacturer in its as processed form and after annealing for comparison. Annealing took place for 1 h at 250 °C in a batch reflow soldering oven. The results showed that the onset of plastic flow depends strongly on the manufacturing condition of the copper materials but that the percentage drop-off in flow stress, with respect to operating temperature, is similar for as delivered and annealed copper.